Magnesium batteries : research and applications - Fichtner, Maximilian (Royal Society of Chemistry, 2020)
The book covers scientific and technical challenges in magnesium battery research, bringing together contributions in the field of anodes, cathodes, electrolytes and systems such as the Mg-S cell.
Includes index.
Keywords: Electric batteries -- Materials.; Magnesium -- Electric properties.; elektronické knihy; electronic books